Kynurenine monooxygenase BcKMOL: a key regulator of growth, pathogenicity, and disease control in Botrytis cinerea - Li, Bai; Liu, Xiaoying; Zang, Jinping; Cao, Hongzhe; Si, Helong; Zhang, Kang; Xing, Jihong; Dong, Jingao (Frontiers in Microbiology, 2025)
Kynurenine monooxygenase, a vital rate-limiting enzyme in the kynurenine pathway metabolic branch, has shown promise as a drug target for treating human neurodegenerative diseases. However, the role of kynurenine monooxygenase in plant pathogens and its potential as a molecular target have received limited attention. In this study, we identified a novel kynurenine monooxygenase gene, BcKMOL, in Botrytis cinerea. By generating mutants of this gene, it was found that the deletion of BcKMOL affected the changes of key metabolites in the kynurenine pathway in vivo, and the △BcKMOL mutant exhibits reduced growth and fails to produce sclerotia. Additionally, changes were observed in the morphology of mycelium cells and spores, and the mutant’s pathogenicity was weakened. These findings indicate that BcKMOL positively regulates the growth, development, and pathogenic processes of B. cinerea. Furthermore, we screened two antibacterial peptides, CAMPQ3966 and CAMPQ4589, that target BcKMOL using MEGADOCK, HDOCK, and AlphaFold3. Both peptides effectively inhibited the pathogenicity of B. cinerea. These findings provide the foundation for developing novel drug targets for controlling gray mold.